(untitled) (Journal of actual problems of jurisprudence, 2019)
The mechanism of protection of civil rights acts in a political, social, socio-psychological context, which may reduce the effectiveness of human rights institutions or, conversely, increase their effect. most sophisticated legal mechanisms and procedures will be powerless in the unstable political situation, the collapsing economy, the loss of values, moral degradation, social and national confrontation. These adverse conditions have developed in the present society. Therefore, the work associated with the improvement of the legal means of protecting human rights and freedoms is inseparable from the system of measures to normalize the situation in the country. For such measures must be based on analysis of the reasons for this unfortunate situation and to identify ways to overcome it.